2021
DOI: 10.1109/access.2021.3119668
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Reconfigurable 1-D Periodic Structure in GaAs MMIC With Stopband Switching, Dual-Band Operation and Tuning Capabilities

Abstract: This paper presents a systematic study of a compact and reconfigurable periodic structure in GaAs MMIC technology. Compactness is achieved by the introduction of spiral inductors in a conventional unit cell without disturbing the reactive loading mechanism. The proposed architecture exhibits a 28.3% wider stopband with 62.6% smaller footprint compared to a conventional structure. The compactness and bandwidth improvement in the proposed structure is explained with the help of dispersion and circuit analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Furthermore, on-chip systems appear to offer a solution for integration. Some studies have shown that it is possible to design a reconfigurable on-chip filter [11][12][13] using GaAs technology.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, on-chip systems appear to offer a solution for integration. Some studies have shown that it is possible to design a reconfigurable on-chip filter [11][12][13] using GaAs technology.…”
Section: Introductionmentioning
confidence: 99%